Digital sustainability culture on campus: University students’ awareness of eco-friendly technology and exposure to sustainability initiatives - Aldawsari, Norah D; Alghamdi, Hamdan Mohammed; Abdellatif, Mohamed Sayed; Abdelhafez, Ahmed M M (Research Journal in Advanced Humanities, 2026)
Guided by the Theory of Planned Behavior, the study surveyed 383 students, gauging their knowledge of eco-technologies, attitudes, perceived control, social norms, intentions, and levels of exposure. The survey incorporated open-ended prompts to gather more nuanced feedback. Using the Theory of Planned Behavior, 383 students completed a questionnaire assessing eco-technology knowledge, attitudes, perceived behavioral control, subjective norms, intentions, and exposure, alongside open-ended questions. The findings revealed that the students expressed robust eco-friendly attitudes, felt social support, believed they could act, and voiced firm intentions. Nonetheless, their factual understanding of eco-technology was only middling. All mean respondent ratings on campus engagement with environmental initiatives were below the midpoint of the benchmarks, and comments described uneven involvement with recycling programs, green infrastructure and other eco-initiatives. Results also showed that the students who had prior experience with sustainability initiatives outperformed their peers on every measured dimension. Exposure correlated positively and significantly with each dimension of awareness and was closely tied to the overall awareness index, confirming the expected link between exposure and awareness. The study underscores the importance of using the campus as a "living laboratory" and for intersecting but equitable sustainability exposure in the first year through curricular and co-curricular experiences.